Cartilage Tissue Engineering Using Stem Cells and Bioprinting Technology—Barriers to Clinical Translation - Francis, Sam L.; Di Bella, Claudia; Wallace, Gordon G.; Choong, Peter F. M. (Frontiers in Surgery, 2018)
Abstract There is no long-term treatment strategy for young and active patients with cartilage defects. Early and effective joint preserving treatments in these patients are crucial in preventing the development of osteoarthritis. Tissue engineering over the past few decades has presented hope in overcoming issues involved with current treatment strategies. Novel advances in 3D bioprinting technology have promoted more focus on efficient delivery of engineered tissue constructs. There have been promising in-vitro studies and several animal studies looking at 3D bioprinting of engineered cartilage tissue. However, to date there are still no human clinical trials using 3D printed engineered cartilage tissue. This review begins with discussion surrounding the difficulties with articular cartilage repair and the limitations of current clinical management options which have led to research in cartilage tissue engineering. Next, the major barriers in each of the 4 components of cartilage tissue engineering; cells, scaffolds, chemical and physical stimulation will be reviewed. Strategies that may overcome these barriers will be discussed. Finally, we will discuss the barriers surrounding intraoperative delivery of engineered tissue constructs and possible solutions.